Global overview of short-term alcohol policies: need for global exchange of experience and impact measurement - Basma Al-Ansari; Venkata Lakshmi Narasimha; Beatrice L. Matanje; Enjeline Hanafi; Francina Fonseca; Jenna L. Butner; Jiang Long; Djibril Moussa; Laura Orsolini; Mehdi Farokhnia; Katrine Melby; Preethy Kathiresan; et al. (BJPsych International)
Alcohol use disorder is a global public health concern and national policies are often implemented to help control alcohol consumption and related consequences. Increasingly, many countries are resorting to transient (short-term) alcohol policies which are implemented for a restricted period of time as an action plan for particular events or health-related issues. The COVID-19 pandemic emphasised the need for rapid decision-making and short-term fast-acting policies. This paper discusses contexts in which these transient policies are used and highlights the need for impact measurement and global exchange of experiences. This is particularly important to avoid gaps that the global alcohol industry could utilise to expand its influence and market.